Millennium goals series: the other way. (Journal of Parents and Teachers, 2014)
The International Community has set out to achieve a series of goals this millennium. However, disease and poverty remain too strong pandemics in our present world.
Keywords: Goals of the millennium; disease; poverty; problems.